ANALISIS SEMIOTIK KATA KICCHIN, DAIDOKORO, DAN CHUUBOO DALAM NOVEL â€œKICCHINâ€ KARYA YOSHIMOTO BANANA - Iwan Setiya Budi (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2007)
â€œKicchinâ€ is Yoshimoto Bananaâ€™s monumental work which won literary award in Japan in 1987. This work was a debut of Yoshimoto to begin her career as a Japanese novelist who is famous world wide. Up to now, her work has been translated into twenty seven languages in the world, and in 1993, â€œKicchinâ€ got its best seller in Italy. In 1993, she got â€œMaskâ€ award, an artist award from Italy. New York Times also gave high appreciation to â€œKicchinâ€. It says that by reading â€œKicchinâ€, people will understand the characteristics of Japanese people easily. By using semiotic approach, the writer analyzed the words â€œkicchin, daidokoro, and chuubooâ€ which mean kitchen. In this novel, a room named kitchen has meaning as a place for family gathering, a place for recovering the characters from loneliness and discouragement, and also as a place for the characters to achieve their future.